E-ARBITRAL IN MALAYSIA: ISSUES, CHALLENGES, AND OPPORTUNITIES (UUM Journal of Legal Studies, 2024)
The shift from traditional arbitration to electronic arbitration (hereinafter referred to as “e-arbitration”) has been driven by severalfactors, including the increasing availability of technology and the need for more efficient and cost-effective dispute resolution in aglobalised world. E-arbitration has been well-received because of its remarkable advantages, including increased efficiency, reduced costs, and improved accessibility, making it an attractive alternative to traditional arbitration. However, to date, the adoption of e-arbitration has not been as expected and the legal position surrounding the legitimacy of the electronic arbitral award (hereinafter referred to as “e-arbitral award”) in Malaysia has yet to be established. This requires a careful examination of existing laws and regulations, as well as a careful consideration of potential challenges and opportunities. This article has been grounded in doctrinal legal research where primary and secondary sources were collected through a library-based approach and later examined using critical and analytical approaches. The use of e-arbitration in Malaysia is expected to encounter several legal challenges since it is not yet fully regulated. However, the present study has found that Malaysian national laws, including the current arbitration laws, are relevant, sufficient, and relatively developed to legalise e-arbitral award. It has also discovered several legal loopholes that must be adequately and directly considered by Malaysian lawmakers. This will enhance the sustainable establishment of e-arbitration in Malaysia and ensure the protection of the interests and rights of all parties involved. Finally, this study has proposed two models for predicting e-arbitral award by human-arbitrators and for enforcing e-arbitral award under the auspices of the AIAC.